Performance for Turbo code on Ricean fading channel - YAO Ru-gui1; WANG Yong-sheng1; XU Juan2 (Tongxin xuebao, 2005)
For a given channel estimation variance, a new metric for Turbo decoding on Ricean channel was proposed, and a novel formula for channel reliability factor Lc was concluded. The presented simulation results show that Turbo decoding with the proposed metric can obtain 0.1~0.6dB more code gain than that with the conventional metric. Furthermore, the performance with the modified metric excels under the condition of significant fading factor and small channel estimation variance, and approaches to the performance on the AWGN channel.